ZnO polymer composite based visible blind UV photo detector. (May 2018) - Patra, Subhasish; Ray, Apurba; Roy, Atanu; Sadhukhan, Priyabrata; Pujaru, Swagatalaxmi; Ghorai, Uttam Kumar; Bhar, Radhaballabh; Das, Sachindranath
Graphical abstract: Highlights: The spherically shaped ZnO NPs with uniform size (∼40 nm) were synthesized. Optical and the UV detection properties of polymer composites were measured. ZnO-PVP sample has the potential as a material for visible blind photo detector. Dielectric medium perturbs electron-phonon interaction and UV detection mechanism. Abstract: Spherical ZnO nanoparticles with average diameter ∼50 nm are synthesized by hydrothermal method. Composites of the nanoparticles with different polymers have been prepared and UV detection properties are measured. The dielectric medium perturbs electron-phonon interaction as well as the optoelectronic properties. Moreover, the luminescence properties of the materials effected due to composite formation. In case of NP-polymer composite NPs are capped and there is negligible further adsorption and desorption of O2 molecules occurred on the surface. This increases the photocurrent as well as photosensitivity. For ZnO based photo detector, there is a small but not negligible photo response near 620 nm. The photo response in this particular wavelength is not observed in case of ZnO-PVP composite and it can be used as visible blind UV detector.